Late Cretaceous paleogeography of the Antarctic Peninsula: New paleomagnetic pole from the James Ross Basin - Milanese, Florencia Nidia; Rapalini, Augusto Ernesto; Slotznick, Sarah P.; Tobin, Thomas S.; Kirschvink, Joseph; Olivero, Eduardo Bernardo (Journal of South American Earth Sciences)
Two paleomagnetic poles of 80 and 75 Ma have been computed from 191 to 123 paleomagnetic samples, respectively, of the marine sedimentary units of the Upper Cretaceous Marambio Group exposed in the James Ross Island, Antarctic Peninsula. Paleomagnetic behaviors during stepwise thermal demagnetization and rock magnetic analyses indicate that magnetization is likely primary and carried by SD-PSD detrital titanomagnetite. Application of an inclination shallowing correction by the elongation-inclination method yielded a significant inclination shallowing affecting the older (ca. 80 Ma) succession exposed in the northwest area of the island. However, the paleomagnetic directions computed from the younger (ca. 75 Ma) succession outcropping in the southeast corner of the island yielded an indeterminate result using the same analysis. The inclination shallowing-corrected 80 Ma paleopole position plus previous ones of ca.110, 90 and 55 Ma were used to construct the Apparent Polar Wander Path (APWP) for the Antarctic Peninsula during the Late Cretaceous-Paleocene. This path confirms that oroclinal bending of the Antarctic Peninsula as well as relative displacement with respect to East Antarctica are negligible since 110 Ma. Comparison with the apparent polar wander path for South America for the 130-45 Ma period suggests that this continent and the Antarctic Peninsula kept a very similar relative paleogeographic position since 110 Ma until 55 Ma, which likely meant a physical link between both continental masses. During that period, both continents underwent a relatively fast southward displacement of around 7° and a clockwise rotation relative to the Earth spin axis that can be bracketed between around 100 and 90 Ma. Oroclinal bending of the Fuegian Andes was likely due to tectonic interactions between the Patagonian-Fuegian Andes and the Antarctic Peninsula promoted, at least partially, by such displacements. By 55 Ma the Antarctic Peninsula probably was starting or about to start its final separation from South ...